Maquinismo, naturaleza y sociedad en el discurso de las cámaras de informes climáticos y de control de tránsito por televisión - Carlón, Mario (CIC. Cuadernos de Información y Comunicación, 2009)
The author of the text analysis how the appearance of the new media of representation, from the painting systems, perspectivistic and based on the ocular vision, and arriving at the photographic devices as an important factor of change, have all affected deeply the essential basis of our public social space, its mediation and its representing image. The complex link between mechanistic representing media, and the social and natural environment, can be studied through the most diverse human activities such as the art, the social and political movements, the writing activities or even the cartoons, as all of them are social operations that produce social meaning, all of them are social specifical practices affected by the diverse new media and their technological effect. The author deepens into how technical devices produce an effect of machinist discourse, specially important in the semiotic processes in society which affect to our way of seeing and living our social world and of constructing its discourses.